2011
DOI: 10.1002/mds.23808
|View full text |Cite
|
Sign up to set email alerts
|

Validation of digital spiral analysis as outcome parameter for clinical trials in essential tremor

Abstract: Essential tremor, one of the most prevalent movement disorders, is characterized by kinetic and postural tremor affecting activities of daily living. Spiral drawing is commonly used to visually rate tremor intensity, as part of the routine clinical assessment of tremor and as a tool in clinical trials. We present a strategy to quantify tremor severity from spirals drawn on a digitizing tablet. We validate our method against a well-established visual spiral rating method and compare both methods on their capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 23 publications
4
105
0
Order By: Relevance
“…Furthermore, these improvements were clinically evident and confirmed by patient observations. The findings also underscore the importance of using an unbiased objective measure of tremor that is highly sensitive and does not rely on highlytrained raters to ensure validity [10]. The safety profile of 1-octanol in this study was consistent with prior reports [5,6] and showed 1-octanol to be well tolerated, with mild side effects, such as headache, gastrointestinal discomfort, and nausea in less than a quarter of participants.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, these improvements were clinically evident and confirmed by patient observations. The findings also underscore the importance of using an unbiased objective measure of tremor that is highly sensitive and does not rely on highlytrained raters to ensure validity [10]. The safety profile of 1-octanol in this study was consistent with prior reports [5,6] and showed 1-octanol to be well tolerated, with mild side effects, such as headache, gastrointestinal discomfort, and nausea in less than a quarter of participants.…”
Section: Discussionsupporting
confidence: 85%
“…Subjects were asked to draw Archimedes spirals in between the lines of a 5-loop template spiral with each hand at multiple time points throughout the observation period. Tremor amplitudes were calculated at the tremor frequency peak after fast Fourier transformation of the spirography time series using published methodology [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Another tool is accelerometry, which informed early propranolol and primidone trials, and there is good correlation between clinical ratings and log-transformed transducer measures of tremor, as predicted by the Weber-Fechner laws of psychophysics [15]. Action tremor can be reliably measured with spiral drawing [16,17]. Maybe in the future modern mobile applications [18] will allow long-duration monitoring of treatment effects, which may be helpful considering minute-to-minute variations of tremors including ET [19].…”
Section: Measurements Of Tremormentioning
confidence: 99%
“…However, side effects are common and frequently doselimiting (see below). The average study cohort size was 18 adults (range, [11][12][13][14][15][16][17][18][19][20][21][22], and thus similar to beta blocker studies, but many randomized patients in studies did not complete the trials. Besides drowsiness and dizziness reported by most patients on total daily dosages of 500 mg or more, children, elderly, and patients with comorbid psychiatric disorders are prone to develop depression, cognitive, and behavioral effects.…”
Section: Primidonementioning
confidence: 99%
“…Our most recent work [13] explored the pharmacokinetics of 2 formulations of 1-octanol at 64 mg/kg and demonstrated that 1-octanol was rapidly metabolized to octanoic acid. The temporal profile of octanoic acid plasma concentrations closely matched the clinical tremor reduction measured using objective spirography [14]. Based on the identification of a potentially novel category of carboxylic acid-based tremor suppression agents, our aim in this study was to test whether octanoic acid demonstrated tremor suppression properties in the rodent harmaline model of ET.…”
Section: Introductionmentioning
confidence: 73%